The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10081662
|View full text |Cite
|
Sign up to set email alerts
|

Chemsex Practices and Health-Related Quality of Life in Spanish Men with HIV Who Have Sex with Men

Abstract: Chemsex, a new risky sexual behavior involving participation in sexual relations under the influence of drugs, has shown a significantly increased prevalence in recent years. This fact entails a serious public health issue, especially when Chemsex is practiced by individuals with an HIV (Human Immunodeficiency Virus) diagnosis. Hence, analyzing the characteristics of Chemsex practices, associated sexual practices and the health outcomes of individuals who participate in Chemsex, is extremely important. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The overall prevalence of chemsex participation among MSM varies widely with one meta-analysis estimating an overall prevalence of 2–28% ( 27 ). Conversely, Ruiz-Robledillo et al reported higher rates of chemsex among PrEP users in Spain at 40.6 and 63%, respectively ( 28 , 29 ). However, chemsex was less frequent (13%) in our study population and only 1 patient reported intravenous recreational drug usage.…”
Section: Discussionmentioning
confidence: 93%
“…The overall prevalence of chemsex participation among MSM varies widely with one meta-analysis estimating an overall prevalence of 2–28% ( 27 ). Conversely, Ruiz-Robledillo et al reported higher rates of chemsex among PrEP users in Spain at 40.6 and 63%, respectively ( 28 , 29 ). However, chemsex was less frequent (13%) in our study population and only 1 patient reported intravenous recreational drug usage.…”
Section: Discussionmentioning
confidence: 93%
“…This ensures that people are prepared to participate in a wide range of sexual acts, which sometimes go beyond their limits [ 2 ]. Chemsex has been associated with high-risk sexual behaviors, including group sex; condomless anal intercourse; fisting; bondage, discipline, sadism, and masochism; having a high number of sexual partners; long sexual sessions that can lead to rectal and penile trauma; and transactional sex [ 2 , 7 , 18 , 26 , 63 , 66 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…On another note, it is crucial to remember that HIV remains a global health issue, especially among the MSM population. Despite the progress made with pre-exposure prophylaxis (PrEP), a false sense of confidence has led to the neglect of barrier methods during sexual relations, resulting in an increase in other STIs such as gonorrhea, syphilis, hepatitis, urethritis, chlamydia, and genital warts [ 11 , 18 ]. The prevalence of “chemsex” among HIV-infected MSM is high, and conversely, the prevalence is lower among stable partners [ 8 , 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%